Pengaruh Kapitalisasi Jakarta Islamic Index (Jii) Dan Indeks Saham Syariah Indonesia (Issi) Terhadap Outstanding Sukuk Korporasi Di Indonesia Tahun 2015-2017 - yurda indari (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2018)
This study analyzes the influence of Islamic stocks on corporate sukuk. The object of this study is the outstanding corporate sukuk in Indonesia in 2015-2016. This study aims to analyze the effect of Islamic stock variables, namely the capitalization of the Jakarta Islamic Index and the Indonesian Islamic Stock Index. This research was conducted using quantitative methods. The data source in this study is secondary data. The data in this study were collected in two ways, namely choosing objects based on three elements (social situation) and samples (purposive sampling). The data collection technique in this study is documentation. The results of this study indicate that the Capitalization of the Jakarta Islamic Index (JII) has a significant negative effect on outstanding sukuk because the capitalization coefficient of the Jakarta Islamic Index (JII) is -0.015194 and the significance level of JII is 0.0299 smaller than alpha 0.05. This means that the increase in capitalization that occurred in 2015-2017 had a significant negative effect on the outstanding sukuk which caused the outstanding sukuk to decline. The Capitalization of the Indonesian Sharia Stock Index (ISSI) has a significant positive effect on outstanding sukuk because the capitalization coefficient of the Indonesian Sharia Stock Index (ISSI) is 0.014341 and the significance level of the ISSI is 0,0008 smaller than alpha 0.05 which means an increase in ISSI capital in the year 2015-2017 had a significant positive effect on outstanding sukuk which resulted in outstanding sukuk increasing.